THE INFLUENCE OF RELIGIOSITY AS A MEDIATING FACTOR IN THE RELATIONSHIP BETWEEN TRUST AND KNOWLEDGE ON SAVING INTEREST IN SHARIA BANK CUSTOMERS - Irdiana, Sukma; Kurniawan Yunus Ariyono,; Kusnanto Darmawan,; Mohammad Noor Khairullah, (Journal of Innovation Research and Knowledge, 2024)
This study aims to determine the relationship between trust and knowledge on the interest in saving of Islamic bank customers in Lumajang, with a focus on generation Z. Respondents numbered 200 respondents spread across Lumajang. Data were collected through an online questionnaire distributed using Google Form. Data analysis was carried out using path analysis with the help of SPSS 21.0 software. The results of the study indicate that knowledge has a direct but insignificant effect on religiosity. trust has a significant direct effect on religiosity. In addition, trust, knowledge and religiosity have a significant direct effect on interest in saving. Another finding is that trust and knowledge do not affect interest in saving through religiosity. This finding indicates that although trust and knowledge factors are important, when associated with the aspect of religiosity, their effect on interest in saving becomes less effective. Therefore, increasing interest in saving may be more effectively achieved through a direct approach to trust and knowledge without having to go through the variable of religiosity as a mediator.